A Numerical Study of the Spring-Back Phenomenon in Bending with a Rebar Bending Machine. (13th October 2014) - Choi, Chang Hwan; Kulinsky, Lawrence; Jun, Joon Soo; Kim, Jin Ho
Abstract : Recently, the rebar bending methodology started to change from field processing to utilizing rebar bending machines at plant sites prior to transport to the construction locations. Computerized control of rebar plant bending machines provides more accurate and faster bending of rebars than the low quality inefficient field processing alternative. The bending process involves plastic deformation of rebars, where bending stress beyond the yield point of the material is applied. When the bending stress is removed, spring back is caused by the elastic restoring stress. Therefore, an accurate numerical analysis of the spring-back process is required to reduce the bending process errors. The most sensitive factors affecting the spring-back process are the bending radius, the bending angle, the diameter of the rebar, the friction coefficient, and the yielding strength of material. In this paper, we suggest a numerical modeling method using these factors. The finite element modeling of the dynamic mechanical behavior of the material during bending is performed using a commercial dynamic analysis program "DAFUL." We use the least squares approach to derive the spring-back deflection as a function of the rebar bending parameters.